Decompression procedure as a successful initial approach to a large maxillary dentigerous cyst in a 12-year-old boy – a case report - Stevanović, Momir; Vujović, Sanja; Mladenović, Raša; Mikić, Mirko; Vasović, Miroslav (Vojnosanitetski pregled, 2023)
Introduction. A dentigerous cyst is a pathological lesion associated with the crown of the unerupted or impacted tooth. Decompression is proposed as the initial treatment for large cysts, especially in younger patients. The aim of this study was to present clinical, radiological, histopathological, and therapeutical aspects of the large dentigerous cyst in the maxilla. Case report. A 12-year-old boy with a large dentigerous cyst in the maxilla was referred to our clinic. A dentigerous cyst was associated with the crown of the unerupted maxillary left canine. Management of the cyst included initial decompression with biopsy, followed by secondary enucleation after 9 months and orthodontic treatment. Histopathological examination confirmed the definitive diagnosis of the dentigerous cyst. Conclusion. Initial decompression with a subsequent enucleation proved to be an effective treatment of choice for the large dentigerous cyst.
Keywords: child; decompression, surgical; dentigerous cyst; diagnosis; maxilla; oral surgical procedures